The prevalence of pap smear screening and association with knowledge, attitude and practice in Kota Kinabalu, Sabah, Malaysia / Yasohdha Anne Sundraraj ... [et al.] - Sundraraj, Yasohdha Anne; Abdul Murad, Noor Shaqirah; Ismail, Nurul Azira; Abdul Rahman, Noor Izzah (2019)
In Malaysia, cervical cancer is the second most common cancer among women. There is an expectancy for the rate of cervical cancer to increase yearly. However early detections can decrease the morbidity and mortality caused by cervical cancer. Papanicolaou (Pap) smear screening has been an important tool to combat cervical cancer. It has been known to be effective, efficient, low in cost and easy to perform in mass testing. Malaysia is composed of two regions which is Peninsular Malaysia and Borneo Malaysia (Sabah and Sarawak). There is a vast difference between the healthcare facilities, economy status and geography conditions mainly the rural areas. As Sabah was reported to have the second most reported case in cervical cancer in Malaysia, this study aims to determine the prevalence of Pap smear screening and its association with knowledge, attitude and practice in Kota Kinabalu, Sabah, Malaysia. A cross-sectional study was conducted which involve 246 women from Kota Kinabalu, Sabah and a subsequent statistical analysis was performed by SPSS version 23. Results indicated that a large number of woman did not perform the Pap smear test although having high level of knowledge (0.783±0.265) and moderate level of attitude (0.633±0.151) towards this matter. This brings the practice to a low level (0.296±0.415) towards performing the Pap smear screening (p<0.05). In conclusion, it can be seen that that the low prevalence of pap smear screening among woman in Kota Kinabalu, Sabah is correlated with practice, although having good level of knowledge and attitude towards pap smear screening and the related health issue matters, many have opted not to perform the screening due to several social factors.